A Review of the Impact of Stevia Leaf (Stevia rebaudiana Bert.) as a Sweetener in Blood Glucose in Alloxan-Induced Rats - Putri, Refitha Nurul; Husni, Patihul (Department of Biological Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, 2024)
Diabetes mellitus (DM) is a chronic condition characterized by elevated blood glucose levels due to insulin-related deficiencies and is often referred to as “The Silent Killer”. Medicinal plants have been widely explored as alternative therapies for managing DM. Among these, Stevia rebaudiana Bert. has garnered significant attention for its potent antidiabetic properties. Known as a natural sweetener 200–300 times sweeter than sucrose, Stevia boasts a zero glycemic index, making it particularly suitable for individuals with diabetes. This review aims to evaluate the antihyperglycemic potential of Stevia rebaudiana Bert. as an alternative to conventional therapies. A systematic review was conducted by acquiring data from scientific databases such as Semantic Scholar, PubMed, Scopus, OpenAlex, Crossref, and ScienceDirect, focusing on literature published between 2020–2024. Studies on diabetic rat models induced with alloxan were analyzed, with doses ranging from 20–1000 mg/kgBW and optimal doses identified between 120–150 mg/kgBW. The results demonstrated that Stevia significantly reduced blood glucose levels in diabetic rats and sustained hyperglycemia, effectively modeling type 1 diabetes. The bioactive constituents, including phenolics, alkaloids, glycosides, steviosides, flavonoids, and tannins, were identified as key contributors to its antihyperglycemic activity. In conclusion, Stevia rebaudiana Bert. exhibits promising efficacy as a natural antidiabetic agent. Its ability to reduce blood glucose levels and its zero glycemic index position it as a viable alternative to conventional antihyperglycemic therapies, especially for managing type 1 DM.